Growth, reproductive performance, and morphometric variation of hybridized Clarias gariepinus burchell, 1822 × Clarias macromystax günther, 1864 in Nigeria - Dadile, Abdulrahman Muhammad (2022)
This study was conducted to examine the hybrid between two African catfish C. gariepinus and C. macromystax using induction breeding. Clarias gariepinus is the most popular aquaculture species in Nigeria and the second most popular in Africa which is gaining attention from both the government and private sectors in Nigeria. The rapid growth rate, adaptation to adverse environmental conditions and diversity make this species an ideal candidate for aquaculture, especially in sub-Saharan Africa. The lack of sufficient quality seed stock is considered to be one of the major obstacles to the development of Clariid catfish farming. Morphological and meristic measurements were carried out on the parent, with F1 and hybrid progeny. Fecundity and gonadosomatic indices of parent species were evaluated and calculated using standard procedures. Growth performance at different growth stages, in two rearing conditions indoors (hatchery) and outdoors (happa net), was evaluated. The results show that both species have the same gonadosomatic index. The male parent species C. garepinus has significant male reproductive quality (P < 0.05) compared to the male parent species C. macromystax. Fecundity was higher (P < 0.05) in the female parent species C. macromystax and lower in the female parent species C. gariepinus. The highest fertilization rate and hatching rate were achieved in the hybrid cross (♀C. macromystax x ♂C. gariepinus) (♀Cm x ♂Cg). The highest rate of deformed larvae was recorded in the hybrid hybrid C. gariepinus x C.macromystax (♀Cg x ♂Cm) and the lowest deformed larvae was achieved in the hybrid hybrid ♀Cm x ♂Cg. The survival rate at the larval stage is more than 70% with the highest survival record in the ♀Cm x ♂Cg hybrid compared to the reciprocal hybrid (♀C. gariepinus x ♂C. macromystax) (♀Cg x ♂Cm) which recorded the lowest value. However, the survival rate at the offspring level is lower than 65% with the highest rate in the ♀Cm x ♂Cg hybrid hybrid followed by the ♀Cg x ♂Cg F1 parent and the lowest survival rate recorded in the cross parent ♀Cm x ♂Cm. Gonadal cross-sections of F1 progeny from parent C. gariepinus and C. macroystax showing testes with well-developed seminiferous tubules and welldeveloped germinal epithelium. Ovaries also have mature ovum in the ovarian tissue. However, the F1 hybrid ova were detected in various stages of development and the testes had sparse germ cells with seminiferous tubules that were not fully expanded indicating that their gonads were still immature at the end of eight (8) months of study. Observation of advanced stages of spermatogenesis and mature spermatoogonia in the gonads of F1 hybrid progeny indicates that, F1 reciprocal hybrids are not sterile but may have the capacity to reproduce. Growth performance at the offspring stage was not significantly different in C. gariepinus parents (♀Cg x ♂Cg) and F1 hybrid hybrids (♀C. macromystax x ♂C. gariepinus) (♀Cm x ♂Cg) compared to C. macromystax parent hybrids (♀Cm x ♂Cm) and a cross (♀C. gariepinus x ♂C. macromystax) (♀Cg x ♂Cm). Similar observations were recorded, at the juvenile to adult stage where final weight, weight gain and heterosis for growth were better in the ♀Cm x ♂Cg hybrid. Regardless of the cross considered, the size of heterogeneity is greater in hybrids and the condition factor (K value) is low. The length-weight relationship is significant with a coefficient of determination R2 greater than 0.9. Growth is of the negative allometric type (with b less than 3). Positive heterosis was recorded for survival and growth at all growth stages. This study revealed the potential of hybrids (♀C. macromystax x ♂C. gariepinus) (♀Cm x ♂Cg), and hybridization between female C. macromystax x C. gariepinus is indeed possible and proven to have better growth and survival rates in semi-arid areas, which will contribute to the increased production of Clarias macromystax in captivity in the Semi-arid zone of Nigeria.